Internet of things mathematical approach for detecting brain tumor - Kareem Jumaa, Noor; A.H Mohamad, Auday; Hameed Majeed, Sameer (International Journal of Engineering and Technology, 2018)
Brain is highly important organ which makes us able to walk, breath, and all other activities; without brain lives canâ€™t do all of that. The importance of brain functions made it critical to make any not precisely measured medical action. Currently; computer vision is very important in medical field, where it helps specialists to precisely diagnose and take the right decision before making surgeries. This article worked on accommodating the technology of internet of things (IoT) for serving brain medicine specialist in the field of identifying the need of making surgeries depending on magnetic resonance imaging (MRI) images. Support Vector Machine (SVM) algorithm is used to detect brain tumor and segment it from MRI morphological images. Putting SVM on IoT Thingspeak platform will help brain specialist to diagnose MRI images that are received from MRI computerized system online. The obtained results are compared with same algorithm implemented locally with assist of Matlab program version R2017a. Â Â